TINGKAT SOLVABILITAS PERUSAHAAN ASURANSI JIWA SYARIAH DI INDONESIA - Nur Wachidah Yulianti (UNIB Press, 2020)
This study aims to look at the mean difference of the solvability level of tabarru’ fund of sharia life insurance companies in Indonesia. The population of this research were full fledge life insurance companies from 2014 to 2019. This research was tested data through one-way analysis of variance (ANOVA) test. One way ANOVA test result shown that there is a significant mean difference between sharia life insurance companies in Indonesia at the solvability level of tabarru’ funds.